2007
DOI: 10.1158/1078-0432.ccr-06-2414
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I, Randomized, Open-Label, Parallel-Cohort, Dose-Finding Study of Elacridar (GF120918) and Oral Topotecan in Cancer Patients

Abstract: Purpose: Breast cancer resistance protein (ABCG2) substantially limits the oral bioavailability of topotecan. Coadministration with elacridar, an inhibitor of breast cancer resistance proteinm ediated drug transport, increases the bioavailability of topotecan. The aim of this study was to establish the lowest effective dose of elacridar to obtain maximum oral bioavailability of topotecan and to determine the optimal schedule of coadministration of oral topotecan and elacridar. In the second part of this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 19 publications
7
97
2
Order By: Relevance
“…Elacridar inhibited ABCG2 as well as ABCB1 and has been used in preclinical and clinical settings (38,39). Elacridar can also significantly increase plasma pharmacokinetics and brain distribution of several drugs, including dasatinib (40), gefitinib (41), and sunitinib (42).…”
Section: Discussionmentioning
confidence: 99%
“…Elacridar inhibited ABCG2 as well as ABCB1 and has been used in preclinical and clinical settings (38,39). Elacridar can also significantly increase plasma pharmacokinetics and brain distribution of several drugs, including dasatinib (40), gefitinib (41), and sunitinib (42).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] However, none of them was approved for clinical use due to their unwanted side effects.…”
mentioning
confidence: 99%
“…Such intestinal drug efflux mediated by BCRP may hinder gastrointestinal absorption of certain therapeutic agents, including sulfasalazine and topotecan (Kuppens et al, 2007;Yamasaki et al, 2008), as suggested by analysis of ABCG2/BCRP gene polymorphisms in combination with the use of BCRP-inhibitory drugs. Nevertheless, there have been few reports regarding post-transcriptional regulatory mechanisms involving physical interaction with BCRP in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane permeation of lipophilic drugs generally occurs by simple diffusion through the lipid bilayer, but absorption of some drugs is hindered by efflux transporters localized on the apical membranes. These include multidrug resistance protein (MDR1/P-glycoprotein/ABCB1) and breast cancer resistance protein (BCRP/ ABCG2), both of which are known to act a barrier against intestinal absorption of various therapeutic agents in vivo (Greiner et al, 1999;Kuppens et al, 2007;Schwarz et al, 2007;Yamasaki et al, 2008;Keskitalo et al, 2009). On the other hand, intestinal membrane permeation of some drugs is mediated by influx transporters that belong to the solute carrier (SLC) superfamily.…”
Section: Introductionmentioning
confidence: 99%